Preliminary evaluation of a microfluidic device for blood separation and deformation assessment - Faustino, Vera (2017)
This work was supported by FCT with the reference project UID/EEA/04436/2013, by FEDER funds through the COMPETE 2020 – Programa Operacional Competitividade e Internacionalização (POCI) with the reference project POCI-01- 0145-FEDER- 006941. V. Faustino and S.O. Catarino thank, respectively, the FCT for the grants SFRH/BD/99696/2014 and SFRH/BPD/108889/2015, supported by national funds from Ministérios da Ciência, Tecnologia e Ensino Superior and by FSE through the POCH - Programa Operacional Capital Humano.